North‐West European MIS 11 malacological successions: a framework for the timing of Acheulean settlements. (18th August 2015) - Limondin‐Lozouet, N.; Antoine, P.; Bahain, J.‐J.; Cliquet, D.; Coutard, S.; Dabkowski, J.; Ghaleb, B.; Locht, J.‐L.; Nicoud, E.; Voinchet, P.
ABSTRACT: Apart from a few lacustrine sequences, in North‐West Europe the Marine Isotope Stage (MIS) 11 interglacial is mainly represented in fluvial sequences and is particularly well preserved in calcareous tufa formations. These are favourable for the preservation of a range of fossil groups and several of them have yielded artefacts of Acheulean affinity. Molluscan shells are the most abundant proxy, occurring throughout these calcareous deposits. They provide a valuable means for reconstructing the palaeoenvironments contemporaneous with human occupation, allowing direct comparisons between sites. The La Celle tufa (northern France) provides the longest malacological succession, which allows a detailed reconstruction of the development of forest cover. Successive arrivals of forest species, first from an Atlantic corridor and later from central and southern European routeways, allow characterization of vegetational development. The initial immigrants indicate the spread of closed habitats, while a peak in the diversity of thermophilous snails corresponds to the optimum phase of deciduous forest expansion. A subsequent decrease in forest molluscs, together with expansion of hygrophilous species, indicates the decline of closed canopy conditions. The occurrence of critical forest species, especially those now extinct or occurring far beyond their modern ranges, provides a framework within which associated Acheulean industries can be set.